True conversions from RAS mutant to RAS wild-type in circulating tumor DNA from metastatic colorectal cancer patients as assessed by methylation and mutational signature. (1st June 2021) - Nicolazzo, Chiara; Barault, Ludovic; Caponnetto, Salvatore; De Renzi, Gianluigi; Belardinilli, Francesca; Bottillo, Irene; Bargiacchi, Simone; Macagno, Marco; Grammatico, Paola; Giannini, Giuseppe; Cortesi, Enrico; Di Nicolantonio, Federica; et al.
Abstract: The paucity of targeted treatments available in patients with RAS mutant colorectal cancers contributes to the poor prognosis of this patient group compared to those with RAS wild-type disease. Recent liquid biopsy-driven studies have demonstrated that RAS mutant clones might disappear in plasma during the clonal evolution of the disease, opening new unforeseen perspectives for EGFR blockade in these patients. Nevertheless, the lack of detection of RAS mutations in plasma might depend on the low amount of released circulating tumor DNA (ctDNA), making it necessary a more accurate selection of patients with true RAS mutation conversions. In this liquid biopsy-based study, we assessed RAS mutational status in initially RAS-mutant patients at the time of progressive disease from any line of therapy and investigated the incidence of true conversions to plasma RAS wild-type, comparing a colon cancer specific methylation profile with a mutational signature of ctDNA. Globally, considering either mutational panel or methylation profile as reliable tests to confirm or exclude the presence of ctDNA, the percentage of "true RAS converters" was 37.5%. In our series we observed a trend toward a better PFS in patients who received anti-EGFR as second or subsequent treatment lines compared to those who did not. Highlights: RAS mutant colorectal cancer patients often switch to RAS wild-type at progression. The presence of ctDNA in plasma must be confirmed by NGS or methylation assay. Clinical trials are currently ongoing to evaluate the efficacy of EGFR blockade in RAS converters.